Dinamika Perubahan Sosial Dan Munculnya Pelecehan Seksual Di Ruang Digital : Analisis Sosiologi Hukum Dengan Pendekatan Teori Cultural lag William F.Ogbrun - Kartika Kartika; Agusmidah Agusmidah; Dedi Haryanto (Journal of Innovative and Creativity, 2025)
Digital technology has transformed patterns of social interaction, shifting communication from physical interactions to activities within digital spaces. This transformation accelerates social change and simultaneously leads to new forms of gender-based violence, including online sexual harassment or technology-facilitated gender-based violence. This research aims to analyze: (1) how digital technological development influences social change and contributes to the emergence of online sexual harassment, (2) the gap between technological advancement and the readiness of social values and legal regulations using William F. Ogburn’s Cultural lag theory, and (3) the legal framework and law enforcement mechanisms related to digital sexual harassment in Indonesia, as well as challenges faced by victims in reporting cases. This study uses a normative juridical method with a socio-legal approach and literature review based on reports from APJII (2024), UN Women (2023), Komnas Perempuan (2024), SAFEnet (2024), and relevant legal regulations, particularly Law No. 12 of 2022 on Sexual Violence Crimes. The results show that digital technology creates anonymous spaces that enable perpetrators to commit sexual harassment more freely. There is a cultural lag between rapid technological advancement and the development of social norms and legal regulations, leading to enforcement challenges such as victim blaming, digital evidence complexity, and low digital literacy among law enforcement. It is concluded that while the Sexual Violence Crimes Law provides a clearer legal framework, further efforts are required to improve digital literacy and victim-centered law enforcement.